Pityriasis Rosea and Pityriasis Rosea-Like Eruption Following COVID-19 Vaccination: A Narrative Review - Potestio L; Martora F; Cacciapuoti S; Megna M; Villani A; Ruggiero A (Dove Medical Press, 2024)
Luca Potestio,* Fabrizio Martora,* Sara Cacciapuoti, Matteo Megna, Alessia Villani, Angelo Ruggiero Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy*These authors contributed equally to this workCorrespondence: Angelo Ruggiero, Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Napoli, 80131, Italy, Tel +39 - 081 - 7462457, Fax +39 - 081 - 7462442, Email angeloruggiero1993@libero.itAbstract: COVID-19 pandemic completely changed every aspect of human life. Several measures were adopted to limit the spreading of the infection. Among these, vaccination was the main one. Globally, vaccination campaign was a success, showing to be efficient in controlling and preventing the SARS-Cov2 infection, reducing the risk of disease progression, hospitalization, and mortality. However, with the increasing number of vaccines administered, several cutaneous reactions were described, making dermatologists key players in their recognition and treatment. Among these, also viral reactivations have been described. In particular, cases of Pityriasis Rosea (PR) and PR-like reactivations have been collected. An early diagnosis is mandatory to avoid mistreatments. In this context, we conducted a review of the current literature investigating cases of PR following COVID-19 vaccination with the aim of understanding the possible pathogenetic mechanisms and causal correlation as well as to investigate the risk of this cutaneous eruption, to offer clinicians a wide perspective on the linkage between PR and COVID-19 vaccines.Keywords: COVID-19, vaccination, pityriasis rosea, safety